2021
DOI: 10.17245/jdapm.2021.21.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intracanal cryotherapy on postendodontic pain: a systematic review and meta-analysis of randomized controlled trials

Abstract: This systematic review aimed to qualitatively and quantitatively evaluate the effectiveness of cryotherapy in the reduction of postendodontic pain. The review question was, "What will be the success rate of cryotherapy technique among human patients with postendodontic pain?". The review protocol was framed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) checklist. Six studies were included in the review, and quantification of five studies was performed through a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
5
2
1
Order By: Relevance
“…After seven days, there was a reduction in the postoperative pain scores in the intracanal cryotherapy group (experimental group) compared with the room temperature group (control group) but this reduction could not be proven statistically due to inestimable MD and CI values. Our results were in contrast with those reported by Gupta et al in their systematic review and meta-analysis where they showed that intracanal cryotherapy did not play a significant role in minimizing postendodontic pain [62]. Pain reduction after cryotherapy application is due to several mechanisms including changes in the nerve conduction velocity, inhibition of nociceptors, and a reduction in the metabolic enzyme activity level [67][68][69].…”
Section: Discussioncontrasting
confidence: 99%
“…After seven days, there was a reduction in the postoperative pain scores in the intracanal cryotherapy group (experimental group) compared with the room temperature group (control group) but this reduction could not be proven statistically due to inestimable MD and CI values. Our results were in contrast with those reported by Gupta et al in their systematic review and meta-analysis where they showed that intracanal cryotherapy did not play a significant role in minimizing postendodontic pain [62]. Pain reduction after cryotherapy application is due to several mechanisms including changes in the nerve conduction velocity, inhibition of nociceptors, and a reduction in the metabolic enzyme activity level [67][68][69].…”
Section: Discussioncontrasting
confidence: 99%
“…Few studies evaluated the effect of cryotherapy on limited biomarkers with different clinical trials, and several studies showed that the cryotherapy decreased post‐operative endodontic pain in different clinical scenarios (Emad et al, 2021; Mourad et al, 2021). However, the recent systematic reviews and meta‐analyses have emphasized the requirement of standardized randomized clinical trials adhering to more clear and strict criteria, randomisation and blinding to clearly define the efficacy of cryotherapy in the management of post‐operative pain (Almohaimede & Al‐Madi, 2021; Gupta et al, 2021; Monteiro et al, 2021). In this randomized controlled trial, intracanal cryotherapy significantly decreased interappointment pain scores and caused different concentration of tested biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent systematic reviews and meta‐analyses emphasized further randomized controlled clinical investigations are required to evaluate the efficacy of the technique (Almohaimede & Al‐Madi, 2021; Gupta et al, 2021; Monteiro et al, 2021). This randomized controlled study aimed to investigate the effect of intracanal cryotherapy on the IL‐1β, IL‐2, IL‐6, IL‐8, PGE 2 , TNF‐α and MMP‐8 levels in the periapical exudate of mandibular pre‐molar teeth with asymptomatic apical periodontitis, to compare cryotherapy and control groups in terms of interappointment and post‐operative pain level and analgesic intake, and investigate a possible the correlation between biomarker levels and interappointment endodontic pain.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the effects of cryotherapy in endodontics, recent systematic reviews with meta-analyses have produced contradictory results. This discrepancy is likely due to the inclusion of randomized controlled trials with methodological deficiencies [ 24 ] or those deemed to provide low-quality evidence [ 25 ]. According to quantitative analysis, intracanal cryotherapy does not seem to significantly reduce post-endodontic pain [ 26 ].…”
Section: Discussionmentioning
confidence: 99%